2016
DOI: 10.1186/s13071-016-1892-8
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Calicophoron daubneyi and Fasciola hepatica in Galicia (Spain): Temporal follow-up in the intermediate and definitive hosts

Abstract: BackgroundParamphistomosis caused by Calicophoron daubneyi and fasciolosis caused by Fasciola hepatica are common parasitic diseases of livestock animals. Transmission of the diseases depends on the presence of intermediate hosts, i.e. freshwater gastropods such as lymnaeids. We carried out a 2-year-long study of the dynamics of the snail population acting as the intermediate host for these parasites, considering the population structure in terms of size/age and infection status. In addition, we determined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 51 publications
1
19
0
2
Order By: Relevance
“…There are several genera of paramphistomes: Paramphistomum, Cotylophoron, Calicophoron, Bothriophoron, Orthocoelium and Gigantocotyle , of which Paramphistomum is the most common and widespread in ruminants ( Taylor, Coop, & Wall, 2016 ). Paramphistomes (amphistomes) are traditionally regarded as having no clinical significance ( Iglesias-Piñeiro et al., 2016 ). However, heavy infection with immature flukes, which attach to the lining of the upper part of small intestine, may cause severe disease which may even result in death ( Lloyd et al., 2007 , Rolfe et al., 1991 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are several genera of paramphistomes: Paramphistomum, Cotylophoron, Calicophoron, Bothriophoron, Orthocoelium and Gigantocotyle , of which Paramphistomum is the most common and widespread in ruminants ( Taylor, Coop, & Wall, 2016 ). Paramphistomes (amphistomes) are traditionally regarded as having no clinical significance ( Iglesias-Piñeiro et al., 2016 ). However, heavy infection with immature flukes, which attach to the lining of the upper part of small intestine, may cause severe disease which may even result in death ( Lloyd et al., 2007 , Rolfe et al., 1991 ).…”
Section: Introductionmentioning
confidence: 99%
“…This was indicated by the fact that all of the 112 metacercariae that were analysed were identified as C. daubneyi , and almost 56% of the mud snails tested positive for C. daubneyi while only one snail was infected with F. hepatica . Not only does this represent an exceptionally high snail infection rate for C. daubneyi (compared with between 4 and 11% reported from France, the UK and Spain) (Mage et al 2002; Jones et al 2015; Iglesias-Piñeiro et al 2016), but also poses the question whether we are currently witnessing a gradual replacement of F. hepatica by C. daubneyi . A similar development has been reported from France and the UK (Rondelaud et al .…”
Section: Discussionmentioning
confidence: 89%
“…2015; Iglesias-Piñeiro et al . 2016), it is thought that double parasitism may be detrimental to their survival. Eventually, cercariae emerge from the snails and encyst on vegetation to be ingested by the next host during grazing.…”
Section: Introductionmentioning
confidence: 99%
“…In Great Britain, the mean prevalence was less than 2% in more than 52,000 G. truncatula dissected by Ollerenshaw [ 43 ] between 1960 and 1969. In Spain, the prevalence was 11.4% in the 5486 snails dissected by Manga-González et al [ 36 ], but was only 4.4% in the 1141 snails dissected by Iglesias-Piñeiro et al [ 24 ]. A molecular biology study revealed a prevalence of 7.0% in 4733 G. truncatula collected from 70 Swiss farms [ 59 ].…”
Section: Discussionmentioning
confidence: 99%